Liver transplantation with a normothermic machine preserved fatty nonagenarian liver: A case report. (2019) - Manzia, Tommaso Maria; Toti, Luca; Quaranta, Claudia; Blasi, Francesca; Tisone, Giuseppe
Highlights: The ex-situ normothermic machine perfusion provide a successful recondition of nonagenarian liver. Gentle cannulation of hepatic artery is mandatory in order to avoid unwanted intimal damage. In order to minimise post LT hepatic artery thrombosis jeopardy no further risk, as previous multi-trans arterial chemoembolization should be taken. Abstract: Introduction: The use of organs from expanded criteria donors for Liver Transplantation (LT) represents a major challenge. In the current era of Normothermic Machine Perfusion (NMP), donor age boundaries are often overcome and may contribute to reduce the gap between supply and demand of organs suitable for transplantation. We report on a unique case of nonagenarian liver successfully transplanted after NMP. Presentation of case: A fatty previously declined liver graft from nonagenarian male brain death donor underwent NMP (OrganOx Metra ®, UK, Oxford) perfusion at University of Rome Tor Vergata on April 2018. The histology assessment showed 15% macro and 35% micro vescicular steatosis. Liver fulfilled viability criteria after NMP and was thus transplanted. The recipient was a 53 years old male with hepatocellular carcinoma who underwent two previous trans-arterial chemo-embolization. The post-LT AST peak was 1556 U/L; post operative course was characterized by hepatic artery thrombosis that required re-laparotomy and successful thrombectomy. Recipient experienced biliary stricture three months after discharge successfully treated by endoscopic retrograde cholangiopancreatography. At 7 months of follow-up patient has good clinical status and graft function. Discussion: NMP represents a safe approach in order to increase the usage of very old fatty livers, that otherwise would be declined because of the high risk of primary non function and death. Conclusion: Nonagenarian liver recruitment after NMP seems to be feasible but a major attention is advisable on the manipulation and cannulation of hepatic artery in order to avoid intimal damage that can lead hepatic artery thrombosis.